PS-010 Extravasation of anthracyclines: Development of an action algorithm for quick and effective treatment. (14th February 2016) - Morgado, M; Freire, I; Eusébio, I; Ribeiro, J; Guardado, M; Duarte, R; Moras, R; Oliveira, R; Morgado, S; Fonseca, O
Abstract : Background: A potential complication of chemotherapy is vesicant cytotoxic extravasation, such as anthracyclines, which may affect the quality of life of patients. Therefore, fast acting and active treatment is essential. Purpose: The aim of this study was to develop an algorithm for management of anthracycline extravasation, which contains management measures, antidote and treatments that should be supplied. Material and methods: A literature review was performed, by research and analysis of guidelines and articles obtained from PubMed from January 2000 to September/2015, using the terms 'cytotoxic extravasation' and 'extravasation treatment'. Results: The first action is to stop anthracycline infusion immediately, not remove the cannula, disconnect the infusion, and with a new syringe aspirate as much of the infusate as possible. The medical staff on service are then notified and the extravasated drug is identified. Thereafter, the extravasation area is marked and photographed and the cannula is removed. Ice packs, to promote local cooling of the extravasation site, should be applied to the affected area for 20 min with minimal pressure. Pharmacological measures involve intravenous infusion of dexrazoxane, for 1–2 h, into a large vein of an area other than the one affected by the extravasation. Cooling procedures should have been removed from the area at least 15 min before dexrazoxane administration in order to allow sufficient blood flow. Treatment should be given once daily for 3 consecutive days. The first infusion should be initiated as soon as possible, within the first 6 h after the accident. Treatment day 2 and day 3 should start at the same time (±3 h) as day 1. Analgesia should be provided if required. The follow-up and long term management is central. According to the clinical trials and case studies available, correct administration of dexrazoxane prevented skin necrosis and ulceration in up to 98% of patients. Conclusion: The development of algorithms for management of chemotherapy extravasation, which allow a quick and effective intervention, is essential. The developed algorithm is a valuable tool for all hospital services that prepare and administer anthracyclines, contributing to a quick and effective response to episodes of extravasation. References and/or Acknowledgements: Int J Clin Pract 2013;67:244–9 No conflict of interest.